Molecular glue degrader for tumor treatment - Hu, Yuhan; Yan, Yan; Wang, Jiehao; Hou, Jiangxue; Lin, Quande (Frontiers in Oncology, 2024)
Targeted Protein Degradation (TPD) represented by Proteolysis-Targeting Chimeras (PROTAC) is the frontier field in the research and development of antitumor therapy, in which oral drug HP518 Receives FDA Proceed Authorization for its IND Application for Prostate Cancer Treatment. Recently, molecular glue, functioning via degradation of the target protein is emerging as a promising modality for the development of therapeutic agents, while exhibits greater advantages over PROTAC, including improved efficiency, resistance-free properties, and the capacity to selectively target “undruggable” proteins. This marks a revolutionary advancement in the landscape of small molecule drugs. Given that molecular glue research is still in its early stage, we summarized the mechanisms of molecular glue, the promising drugs in clinical trials and diverse feasible design strategies for molecular glue therapeutics.